Fish - DeSombre, Elizabeth R.; Barkin, J. Samuel, 1965- (Cambridge ; Malden, MA : Polity Press, 2011)
"Fishing has played a vital role in human history and culture. But today this key resource faces a serious crisis as most species are being overfished or fished to their very limit. Governments have tried to tackle the problem with limited success. Many of their actions have been counterproductive or ineffective. What will happen to global fisheries, and the populations that depend on them, as we continue to catch more fish than the oceans can reproduce? This book explores the causes of the current crisis in the world's fisheries, and what needs to be done to address the situation. It explains the structure of the fishing industry, the incentives that persuade individuals or companies to catch fish at unsustainable levels, and illuminates the problems created by governmental efforts to use fishing policy as a tool for economic development or to win votes in domestic elections. It also looks at the role of aquaculture in either decreasing or increasing the pressure on wild fish stocks. The dire condition of fish stocks has led governments and consumer organizations to consider new approaches to protect the global supply of fish. DeSombre and Barkin conclude by showing how such methods, along with new forms of international regulation and informed decision-making by consumers, all have an important part to play in rewarding and thus encouraging sustainable fishing behaviour in the future."--pub. website.
Growth of the global fishing industry -- Structure of the fishing industry -- Regulatory efforts and impacts -- Aquaculture -- Consumers and catches.
Includes bibliographical references and index.
Keywords: Fishes -- Conservation; Fishes -- Conservation; Fisheries -- Environmental aspects; Fishery policy; Sustainable fisheries